Prevalence of TMD among Children Provided with Fixed Orthodontic Treatment - Alma Mušanović; Muhamed Ajanović; Lejla Redžepagić Vražalica; Lejla Kazazić; Selma Tosum Pošković; Jasmina Mlačo Durek; Sanela Strujić Porović (University of Zagreb. School of Dental Medicine, 2021)
According to available scientific references and textbooks, there are contradictory views concerning the etiology of signs and symptoms of TMD. Objectives: The aim of this study was to determine a correlation between the incidence of signs and symptoms of TMD in children aged 12-18 who do not wear a fixed orthodontic appliance and the incidence of signs and symptoms of TMD in children who wear a fixed orthodontic appliance. Material and Methods: The total number of 120 subjects were included in this survey and divided into two groups. There were 60 respondents in the experimental group that consisted of 30 boys and 30 girls with different types of malocclusion, who were treated with a fixed orthodontic straight wire technique. The remaining 60 respondents, which was a group that also consisted of 30 boys and 30 girls, were patients with neutroclusion. Results: The results of the study have shown that the TMJ clicking sound symptom, the most common symptom of TMD, occurs with almost equal prevalence in both groups of respondents; specifically, 56.4% in orthodontic patients, and 46.6% in the control group respondents. A statistically significantly higher percentage of female respondents in both groups have experienced headache problems (p <0.03). Conclusion: On the basis of the statistics obtained as a result of this research, we can come to the conclusion that there is no correlation between the fixed orthodontic treatment and the development of signs and symptoms of TMD